A Finite Element Method using COMSOL on ERT Applying Metal Wall Pipe: Effect on the Potential Distribution and Current Streamline - Suzanna, Ridzuan Aw; Ruzairi, Abdul Rahim; Mohd Hafiz, Fazalul Rahiman; Yasmin, Abdul Wahab; Juliza, Jamaluddin; Zulkanrnay, Zakaria; Nurainizzati, Shuhaimi; Farah Hanan, Azimi; Lia Safiyah, Syafie; Damhuji, Rifai (Malaysian Society for Computed Tomography and Imaging (MyCT), 2021)
This paper presents the effect on potential distributions and current streamlines for Electrical Resistance Tomography (ERT) applying metal wall pipe. A conducting boundary approach was applied in the measurement part of the research and COMSOL Multiphysics software has been applied in this work to solve the forward problem of the system. Sixteen electrodes with gold plated material as the conducting surface and FR4 as the insulating material were implemented as the sensing plate in the research. The simulations showed that the sensing field will be deflected based on the conductivity distribution within its sensing region. The electrical potential of the system also varied accordingly.